(3JQLeGf GdCThGb aj GdZRd hGdfSjHs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CTjQ HgG Edi eYGQa QHGfjI hCfhGQ EdgjI hCSQGQ QhMGfjI hYdhe YbdjI hJfHjgGJ TQYjI , hLYdJ GdYHGQI Yf Pdc HdSGf GdZRd hGdfSjH s
(3BNQgG (B:s
(3hjRYehf Cfge jTjQhf Hg Edi Ydhe GUWdMhG YdjgG HgPg GdCdaGX hMSf Xfg hGfJaY acGf SHH TQMi dgPG GdcJGH hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdLRA (B1 - (3U (B396 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B172 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdYHGSjI (B- (3GdHUQI (B(74(3L(B) s
Keywords: (3GdCOHs